2019
DOI: 10.1587/elex.16.20190135
|View full text |Cite
|
Sign up to set email alerts
|

Observation of multimodal interference in millimeter-long polymer optical fibers

Abstract: We observe multimodal interference in single-mode-multimodesingle-mode sensors comprising short polymer optical fibers (POFs) with lengths from 100 mm down to 7 mm. Characteristic spectral peaks/dips are observed not in the conventionally used telecom band but around 1000 nm. We find that the dip wavelength depends on temperature but that the sensitivity is much lower than those obtained in the longer wavelength range when longer POFs are used. We discuss the possibility that, even with the reduced sensitivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Numata et al 9) reported an extremely high-temperature sensitivity of 49.8 nm °C−1 at 1300 nm using a 1.0 m long perfluorinated (PF) graded-index (GI-) POF, 4,[15][16][17] the propagation loss of which is much lower at telecommunication wavelengths than that of a PMMA-based POF. The performance of the PFGI-POF-based SMS sensors has been significantly enhanced so far, [18][19][20][21][22][23][24] while the modal interference in a partially chlorinated POF has also been reported to be of some use in developing temperature sensors. 25) Thus, not a few reports have been provided on the use of materially special POFs, but there have been no reports on the structurally special POFs, including multi-core POFs originally fabricated for the purpose of image transmission.…”
mentioning
confidence: 99%
“…Numata et al 9) reported an extremely high-temperature sensitivity of 49.8 nm °C−1 at 1300 nm using a 1.0 m long perfluorinated (PF) graded-index (GI-) POF, 4,[15][16][17] the propagation loss of which is much lower at telecommunication wavelengths than that of a PMMA-based POF. The performance of the PFGI-POF-based SMS sensors has been significantly enhanced so far, [18][19][20][21][22][23][24] while the modal interference in a partially chlorinated POF has also been reported to be of some use in developing temperature sensors. 25) Thus, not a few reports have been provided on the use of materially special POFs, but there have been no reports on the structurally special POFs, including multi-core POFs originally fabricated for the purpose of image transmission.…”
mentioning
confidence: 99%
“…This behavior was probably caused by the existence of the multiple cladding modes, being analogous to a modal interference sensor based on a single-mode-multimode-singlemode structure. [30][31][32][33][34] This may limit the temperature dynamic range, and on this point, further study is required.…”
mentioning
confidence: 99%